'Facebooked: Romeo and Juliet' as educational theatre: an improbable fiction?. Issue 3 (2nd July 2016) - Zdriluk, Helen
ABSTRACT: This article addresses intersections of digital technology and Drama Education, with attention to an undergraduate playbuilding project focused on digital citizenship. It explores the challenges involved in structuring a technologically interactive presentation, as well as the positive impact of the piece achieved through the interplay of two related contexts: (a) the depiction of social media forms in the text itself and (b) the use of these forms as a medium of presentation. The article suggests further exploration of digital citizenship and intermedial approaches in undergraduate Drama Education programmes.